Conditioning for dance : training for whole-body coordination and efficiency - Franklin, Eric N. (Human Kinetics, 2019)
"An internationally renowned master teacher, Franklin has developed a science-based method of conditioning that is taught and practiced in companies and schools around the world. In this new edition of Conditioning for Dance, he integrates the latest scientific research on strength, flexibility, and conditioning into his dance exercises."--Publisher's description.